Emotional-focused skills as determinants of marital satisfaction among postgraduate students - Lasisi, Adekola Kamil; Shittu, Abdullateef (Universitas Negeri Semarang, 2023)
Marital satisfaction holds paramount importance for postgraduate students, given the profound impact of higher education on emotional well-being. This study investigated emotional-focused skills as determinants of marital satisfaction among postgraduate students at Al-Hikmah University, Ilorin, Nigeria. A descriptive research design of correlation type was used. The population of the study was 1,193 postgraduate students of Al-Hikmah University, Ilorin. The sample was 300 postgraduate students from the Faculty of Education, Al-Hikmah University, Ilorin-Nigeria using the Slovin sample size determination formula. Emotional Focus Skills Questionnaire (EFSQ) and Marital Satisfaction Scale (MSS) duly validated by the owners with the reliability coefficient at Cronbach Alpha of 0.93 and 0.82 were used for the study. Pearson Product Moment Correlation (PPMC) at 0.05 level of significance. Results showed that emotional awareness has a positive relationship with marital satisfaction among postgraduate students at Al-Hikmah University, Ilorin-Nigeria. The study also indicates that emotional regulation has a positive relationship with marital satisfaction among postgraduate students at Al-Hikmah University, Ilorin-Nigeria. The study showed that emotional intelligence has a positive relationship with marital satisfaction among postgraduate students at Al-Hikmah University, Ilorin-Nigeria. The study concludes among others that emotional awareness has a positive relationship with marital satisfaction among postgraduate students at Al-Hikmah University, Ilorin, Nigeria. Based on the conclusion, the study recommends among things that postgraduate schools should hire a professional marriage counsellor to assist postgraduate students with marital challenges; school counsellors should employ the use of emotional-focused counselling skills to help improve awareness and regulate negative emotions to sustain marital satisfaction. This research contributes to the existing literature by specifically examining the relationship between emotional-focused skills and marital satisfaction among postgraduate students, filling a gap in current academic discourse